Functional Laplace operator on a p-adic space and Feynman-kac and Feynman formulas - Nikolaj N Shamarov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2011)
Homogeneous closed PDO are constructed which are analogous to the powers of (absolute value of ) inﬁnite dimensional Laplacian and acting in Banach spaces of complexvalued functions deﬁned on function spaces over a ﬁeld of p-adic numbers. For elements of semigroups, for which these PDOs are generators, Feynman formulas and Feynman-Kac ones are obtained.